On the Efficiency of Destination and Origin Commodity Taxation in the Presence of Consumption Generated Cross-Border Pollution - Fabio Antoniou; Panos Hatzipanayotou; Michael S. Michael; Nikos Tsakiris (Center for Economic Studies and ifo Institute (CESifo), 2016)
We combine consumption generated cross-border pollution and public pollution abatement in a theoretical framework to examine the efficiency of the destination and origin principles of commodity taxation. The key result of our study is that with public pollution abatement, the non-cooperative equilibrium origin-based consumption taxes are set efficiently. This result holds not only in the context of symmetric countries, but under certain conditions carry over also to asymmetric countries. The non-cooperative equilibrium destination-based consumption taxes are inefficient. In the absence of public pollution abatement, the Nash equilibrium commodity taxes under either taxation principle are inefficient.
Keywords: H21; H23; H87; 330; commodity taxation; destination principle; origin principle; cross-border pollution